Investigation Of Robustness Of 18f-Fdg Pet/Ct Radiomics Features For The Development Of Image Based Biomarkers For Head And Neck Cancer - Anan, Noushin (2023)
Conventionally, 18F-FDG PET/CT is evaluated through biomarker matrices for example metabolic tumour volume (MTV) and standardised uptake values (SUVs) for cancer prognosis. However, they do not quantify tumour heterogeneity that induces resistance to treatment. Radiomics may quantify tumour heterogeneity by recognising features and patterns present in the 18F-FDG PET/CT. The radiomics feature of 18F-FDG PET/CT need to be accurate in other words robust for different segmentation settings. This study aimed to investigate the robustness of 18F-FDG PET/CT radiomics features for image-based biomarker development for head and neck cancer diagnosis.